Tax reforms in Latin America 1978-1992 : a comparative analysis. - RODRIGUEZ, Flavia (1994)
Presents an overview of some of the fiscal reforms that have been implemented in Mexico, Colombia, Ecuador, Bolivia, the Dominican Republic, and Paraguay. Examines the reforms to find their common features and their differences, and analyses their contribution to the public finances of the respective countries.